RFImeDia an RFID-enabled space - Barroga, Sicilienne M. (2011)
There has been a tremendous wave of technologies that help everyday activities become convenient to do. These offer "anytime, anywhere, anyone" computing by automatically providing adequate services for users according to their changing preferences. An interesting application is a smart space that adapts to the users? interests and context. Nevertheless, not many spaces have these features. To address this concern, the group implemented and RFID-enabled space. An RFID tag is carried by a user, and each of the two stations in the room has a dedicated RFID reader and a PC station. In addition to this, one IP camera is also deployed in the room. In a remote database, the user has his own record where his basic information and ranked preferences are stored through registration. When the user passes by the PC station for music, the reader identifies the tag and sends the EPC and location ID of the user and when there is, it determines which content is to be played by retrieving the files of the appropriate music genre of his preference. A playback history table in the PC station records the recently played music to help in predicting the next priority genre of user who passes by the object more than once. The remote PC also notifies the IP camera also takes a snapshot and video streams of the area where the person was detected. The same thing happens when the tagged person is detected by reader in the PC station for movie. This is promising as the coverage of this project can extend up to large-scale context-aware services like museums, tour guide systems, and expansion of number of users that can be accommodated.